The golden ratio : the story of phi, the world's most astonishing number - Livio, Mario, 1945- (New York : Broadway Books, 2002)
Tells the story of phi, the never ending, never repeating number known as the Golden Ratio, written as 1.6180339887..., looking at how it has been used, and claims about its use, throughout the history of mathematics.
Includes bibliographical references (p. [270]-277) and index.
Booklist.
Publisher's Weekly.
School Library Journal.
Adult
Keywords: Golden section; Plane geometry; Ratio and proportion